2017
DOI: 10.1016/j.envexpbot.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Developmental age and UV-B exposure co-determine antioxidant capacity and flavonol accumulation in Arabidopsis leaves

Abstract: Developmental age is an important determinant of plant stress responses. In this study the importance of “within-individual-heterogeneity” of developmental age for plant UV-B responses was quantified. Arabidopsis thaliana rosettes were raised under indoor conditions, and the responses of leaves at different developmental stages were compared following exposure to supplemental UV-B radiation. Exposure to a low dose of UV-B had positive effects on concentrations of UV-absorbing pigments, quercetins and kaempfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 43 publications
8
25
0
Order By: Relevance
“…4b ). Consistent with other studies 43 , low dose UV-B significantly increased antioxidant capacity in plants grown in white light. The same UV-B treatment given to coriander grown in low R:FR was, however, ineffective.…”
Section: Discussionsupporting
confidence: 92%
“…4b ). Consistent with other studies 43 , low dose UV-B significantly increased antioxidant capacity in plants grown in white light. The same UV-B treatment given to coriander grown in low R:FR was, however, ineffective.…”
Section: Discussionsupporting
confidence: 92%
“…The response of genes related to secondary metabolite productions to UV-A irradiation is further evidence that the results of the significantly increased total phenol content and antioxidant capacity after 4 and 5 days of UV-A treatment were due to activation of the biosynthetic pathways responsible for the production of secondary metabolites. It has been reported that UV treatment increases flavonoid concentration (Reifenrath and Müller, 2007), UV-absorbing pigments, flavonols, and total antioxidant activity (Csepregi et al, 2017) in leaves of all ages (within a single plant), although there is a difference in the degree of increased. Therefore, the difference in the degree of bioactive compounds increased by UV-A LED treatment is also considered to be negligible, because samples of each parameter were collected from leaves of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the higher ROS-scavenging capacity of phenolics and flavonoids than anthocyanins, resulting in more sensitive reactions of phenolics and flavonoids to UV-B radiation [54]. Csepregi et al (2017) also reported such differential regulation of different phenolic compounds by UV-B radiation, in which quercetins with additional hydroxyl group on ring-B increased up to 10 folds while kaempferol increased 3-4 fold, due to their different ROS-scavenging capacity [55].…”
Section: Impacts Of Uv-b and Ppfd On Phytochemical Accumulation And Amentioning
confidence: 99%